Efficacy and safety of elbasvir/grazoprevir for 8 or 12 weeks for hepatitis C virus genotype 4 infection: A randomized study. (22nd March 2020) - Asselah, Tarik; Pol, Stanislas; Hezode, Christophe; Loustaud‐Ratti, Veronique; Leroy, Vincent; Ahmed, Si Nafa Si; Ozenne, Violaine; Bronowicki, Jean‐Pierre; Larrey, Dominique; Tran, Albert; Alric, Laurent; Nguyen‐Khac, Eric; et al.
Abstract: Background & Aims: Hepatitis C virus (HCV) genotype (GT) 4 infection is prevalent in sub‐Saharan Africa and the Middle East, particularly in Egypt. This study evaluated the safety and efficacy of elbasvir/grazoprevir administered for 8 and 12 weeks in participants with HCV GT4 infection. Methods: In this partially randomized, open‐label multicentre study conducted in France (NCT03111108; Protocol MK5172‐096), treatment‐naive participants with GT4 infection and F0‐F2 fibrosis were randomized 2:1 to elbasvir (50 mg)/grazoprevir (100 mg) for 8 or 12 weeks. Treatment‐naive participants with F3‐F4 fibrosis and all treatment‐experienced participants (F0‐F4) were assigned to elbasvir/grazoprevir for 12 weeks. The primary endpoint was sustained virologic response (SVR) 12 weeks after the end of therapy. Results: One hundred and seventeen participants were enrolled. Among treatment‐naive participants with F0‐F2 fibrosis, SVR was achieved by 94% (50/53) and 96% (26/27) of those receiving elbasvir/grazoprevir for 8 or 12 weeks, respectively, and four participants relapsed. In the 12‐week arm, 95% (35/37) achieved SVR and two participants relapsed. NS5A resistance‐associated substitutions were present at baseline and virologic failure in five of the participants with relapse. Drug‐related adverse events occurred in 42% (n = 22) and 50% (n = 32) of participants receiving 8 and 12 weeks of treatment, respectively. No participant discontinued treatment owing to an adverse event. Conclusion: These data confirm the efficacy of elbasvir/grazoprevir administered for 12 weeks in treatment‐experienced individuals with HCV GT4 infection and those with advanced fibrosis. Treatment‐naive individuals with mild fibrosis can be treated effectively with an 8‐week regimen.